Accounting information systems - Hurt, Robert L.
Hurt's Accounting Information Systems, 2e continues to take a fresh new approach that puts judgment and critical thinking, not technology, at the heart of the AIS course. Using a conversational writing style appealing to students, this book presents AIS as an art as much as a science. "AIS" is presented as a set of fundamental ideas and concepts that can be applied in various organizational contexts. Students are provided with vocabulary they will need to succeed in the profession and ensuring that they can communicate clearly and effectively about accounting information systems with both accountants and nonaccountants. The text end-of-chapter exercises and assessment tools are all competency-based, distilling knowledge to its essential elements and then encouraging students to use those essential elements to think for themselves